Histerese na taxa de desemprego nos estados brasileiros - Lopes, Francisco William Pinheiro (2023)
For years economists have studied the phenomenon of unemployment based on the inverse relationship between the unemployment rate and the level of inflation. However, after the oil shocks of the 1970s, Europe began to have high persistent unemployment rates even with stable inflation during the 1980s. thenceforth, the persistence in the unemployment rate has been studied as a hysteresis phenomenon, where the employment rate suffers from past shocks and has difficulty returning to levels before the shocks. In this study, we elaborated a 9-year quarterly series with the 27 Brazilian states to verify the existence, or not, of a unit root in the data on the unemployment rate series. The results found indicate the presence of hysteresis in most Brazilian states and, thus, a difficulty for this rate to return to equilibrium levels.